A Point-based Histologic Scoring System for Hepatocellular Carcinoma Can Stratify Risk of Posttransplant Tumor Recurrence. (July 2018) - Roberts, Daniel E.; Kakar, Sanjay; Mehta, Neil; Gill, Ryan M.
Abstract : Eligibility for liver transplant is most commonly decided by measuring tumor size and number on radiographic imaging. However, this method often underestimates the extent of disease. Evaluation of tumor histology has been shown to improve risk stratification when compared with imaging-based transplant criteria, but the World Health Organization (WHO) guidelines for grading hepatocellular carcinoma (HCC) are imprecise and require subjective interpretation by the pathologist. We performed a retrospective analysis of 190 explanted livers containing HCC and correlated histologic features with posttransplant recurrence to formulate a three-tiered, point-based scoring system that categorizes tumors as having a low, intermediate, or high risk of recurrence. Our Recurrence Risk Assessment Score (RRAS) evaluates tumor architecture and specific cytologic features—nuclear pleomorphism, cytoplasmic amphophilia, and nuclear-to-cytoplasmic ratio—showing superior stratification of HCC recurrence risk compared with imaging criteria and grade assigned by WHO methodology. Stratifying tumors using RRAS criteria, the rate of recurrence after transplant was 0% among low-risk tumors (compared with 3% of well-differentiated tumors), 12% among intermediate-risk tumors (compared with 15% of moderately differentiated tumors), and 54% among high-risk tumors (compared with 29% of poorly differentiated tumors). Receiver operating characteristic analysis shows significantly improved performance of RRAS criteria in predicting HCC recurrence compared with WHO grade (area under curve of 0.841 and 0.671, respectively; P =0.0061). Our results indicate that evaluation of tumor histology offers superior prediction of recurrence risk following liver transplantation compared with radiographic criteria, and that the RRAS system better stratifies recurrence risk compared with HCC grading by WHO methodology. Abstract : Supplemental Digital Content is available in the text.